Child and adolescent behavioral health a resource for advanced practice psychiatric and primary care practitioners in nursing - Yearwood, Edilma Lynch; Pearson, Geraldine S.; Newland, Jamesetta A. (Wiley-Blackwell, 2012)
"As an increasing number of children and adolescents with psychiatric symptoms go unrecognized in our current health care system, the ability to identify and treat these issues in multiple health care settings has become vitally important. With access to primary care providers increasing and a shortage of child psychiatric providers, collaboration between psychiatric, pediatric and family advanced practice nurses is essential to improving care for this vulnerable population. Child and Adolescent Behavioral Health: A Resource for Advanced Practice Psychiatric and Primary Care Practitioners in Nursing provides a practical reference to aid in this endeavor. Aimed at advanced practice nurses and graduate students in nursing, this book is divided into 4 sections addressing assessment, treatment, special populations, and special issues. Within these sections, each chapter includes state-of-the-art, evidence-based information about the most common issues faced by psychiatric and primary care practitioners alike. Chapters focused on disorders review clinical manifestation, etiology, nursing interventions, integration with primary care, and implications for practice, research, and education. Chapters focused on issues describe the linkages between the behavioral/psychiatric profile of the child and associated risk and management strategies. Written/reviewed by over 70 nurse experts, Child and Adolescent Behavioral Health: A Resource for Advanced Practice Psychiatric and Primary Care Practitioners in Nursing is a must-have reference for all practitioners caring for children and adolescents"--Provided by publisher.